Best practices in urban solid waste management : ownership, governance, and drivers of performance in a zero waste framework /: ownership, governance, and drivers of performance in a zero waste framework. (2021) - Romano, Giulia, 1978-; Marciano, Claudio, 1983-; Fiorelli, Maria Silvia
No abstract available